PEDAGOGICAL PRACTICES IN MATHEMATICS RESEARCH FOR EARLY CHILDHOOD EDUCATION: CONTRIBUTIONS TO TEACHER EDUCATION - Geuciane Felipe Guerim Fernandes; Caroline Subirá Pereira; Flaviane Pelloso Molina Freitas (Universidade do Estado do Rio de Janeiro (UERJ), 2023)
The article aims to characterize the scientific productions that present pedagogical practices of Mathematics for Early Childhood Education and analyze their contributions to the training process of teachers who work in this stage of Basic Education. For this, some questions are necessary: What pedagogical practices are evidenced in research in mathematics for Early Childhood Education? How can these practices contribute to the training process of teachers who work at this stage? For this purpose, a survey was carried out with the descriptors "Mathematics" AND "Child Education". Scopus Platform and Science Direct. From the reading and selection of articles, three categories of analysis were organized. Regarding the analyzed proposals, the results indicate that the constant search for studies, deepening and possibilities are paths that need to be followed by teachers who teach mathematics in Early Childhood Education and by those still in initial training.